Principles and Practices of Plants Genomics - Kole, Chittaranjan; Abbott , Albert G. (New Hampshire : CRC, 2010)
This book presents the basic and applied aspects of sequencing of genes and genomes and their implication in the fine-scale elucidation of the plant genomes. The third volume presents an overview on the advances of plant genomics made in the past century; deliberations on the genomics resources; concepts, tools, strategies, and achievements of comparative, evolutionary, and functional genomics and whole-genome sequencing. It also presents critical reviews on the already completed genome initiatives and glimpses on the currently progressing genome initiatives. This volume is an ideal reference book for students, scholars and scientists in academia, industry, and government.
Includes bibliographical references; Index 583-590p.
Keywords: Plant genetics; Plant genomes